Control of virus and virus-like diseases of fruit crops. UNDP/FAO/RAB/88/025: Present situation and future prospects of the grapevine, citrus and stone fruit networks - Djerbi M. (Proceedings of the Mediterranean network on certification of citrus. 1995-1997, 1998)
A general view on the activities and results of the project is given. The project's major objective is the development of national capacities for production, maintenance and distribution of virus-free crop planting material by the establishment of regional repositories of virus-free fruit crops, the monitoring of virus diseases and the training of plant quarantine personnel. Expert technical advice and technology transfer are to be provided and complemented by training and provision of necessary supplies. Lack of funds prevented the initiation of any significant activities and the objective to harmonize the regulations for plant material registration and certification never materialized. MNCC can become a complementary part of it, including countries (Turkey) not in the Project.
Round Table on: Citrus Virus and Virus-like Diseases and Certification: State of the Art, 1995/07/21, Bari (Italy)